Evaluating potential market acceptance of biomedical services of Pride Outlet Sdn Bhd / Alya Izzatti Azmin, Nik Nur Amalin Nadia Azmi and Nurfarain Hafifie Abd Rashid - Azmin, Alya Izzatti; Azmi, Nik Nur Amalin Nadia; Abd Rashid, Nurfarain Hafifie (Arshad Ayub Graduate Business School, 2018)
Biomedical engineering services has become an important part in the business of health and medical services nowadays. This is due to the increasing demand in the servicing and maintenance of biomedical equipment to ensure that hospitals and their medical facilities are operating smoothly. Although there is persistent demand, biomedical engineering services are not without its problems. For one biomedical engineering service company, Pride Outlet Sdn Bhd, understanding market needs while operating in an industry that is very specialised, has prompted the execution of this study. This study sets out to investigate factors influencing the market acceptance of biomedical services of Pride Outlet Sdn Bhd. Using a qualitative research method, this study interviewed informants of three hospitals to gain their views of biomedical service providers in line with their needs and acceptance of the services. The accumulated information was analysed using the SWOT analysis, TOWS matrix and the CPM profile matrix in gaining a comprehensive understanding of the situation. The findings from the research revealed that competency, resource, arrangement and pricing are the most important factors that contribute to market acceptance. The results of the study suggest that Pride Outlet improve their staff competency which include technical skills and availability of the staff to serve the clients. Moreover, Pride Outlet needs to improve on their ability to provide loan units (equipment) to ensure market acceptance. It is hoped, that this study would help Pride Outlet improve their business strategy to be at par with other competitors.